Shifting paradigms in public health from holism to individualism - Yadavendu, Vijay Kumar (Springer India, 2013)
This transdisciplinary volume outlines the development of public health paradigms across the ages in a global context and argues that public health has seemingly lost its raison d'tre, that is, a population perspective. The older, philosophical approach in public health involved a holistic, population-based understanding that emphasized historicity and interrelatedness to study health and disease in their larger socio-economic and political moorings.